Investigation the Network of Highways of International Importance the Republic of Uzbekistan - Aziz Khalmukhamedov; Kudrat Kutlimuratov (Zien Journals, 2022)
The efficiency of a state economy depends on a quality of highways. One of the important indicators of the quality of roads is road roughness, which determines the possible permissible speed of vehicle movements, as well as the associated traffic safety and cost of transportation. In a comprehensive solution to the problem of reducing the cost of transportation on roads play an important role, not only the costs of repairing and maintaining the roads themselves, but also the costs of organizing traffic safety, repairing and maintaining the vehicles themselves. The lack of data on the actual state of highways does not allow us to determine the rational speed of movement of transports, depending on the specific indicators of the road roughness and the parameters of moving vehicles. The Committee on Roads under the Ministry of Transport of the Republic of Uzbekistan set the task of examining and assessing the entire road network of the country. This study will help establish a list of maintenance priorities and provide reliable data for assessing road performance. At the first stage, the task was set to study the longitudinal road roughness of the network of highways of international importance. Highways of international importance, with a length of slightly more than 9% of the total length of the public road network, provide about 40% of all road transport and 100% of all transit road transport. The paper presents results of a study of the international road roughness the example of the international motor road M39.
Keywords: Transport roads; Highways of international importance; International road roughness; Technical and operational performance of road transport